"Work with me": service users' perspectives on shared decision making in mental health. Issue 3 (11th September 2017) - Castillo, Heather; Ramon, Shulamit
Abstract : Purpose: While shared decision making (SDM) in general health has proven effectiveness, it has received far less attention within mental health practice with a disconnection between policy and ideals. The purpose of this paper to review existing developments, contemporary challenges, and evidence regarding SDM in mental health with a particular focus on the perspectives of service users. Design/methodology/approach: This is a review of international papers analysed using narrative synthesis of relevant data bases. Findings: The review shows significant barriers to the utilisation of SDM including ethical and legal frameworks, accountability and risk. The medical model of psychiatry and diagnostic stigma also contributes to a lack of professional acknowledgement of service user expertise. Service users experience an imbalance of power and feel they lack choices, being "done to" rather than "worked with". Practical implications: The paper also presents perspectives about how barriers can be overcome, and service users enabled to take back power and acknowledge their own expertise. Originality/value: This review is the first with a particular focus on the perspectives of service users and SDM.